Edge effect enhanced electron field emission in top assembled reduced graphene oxide assisted by amorphous CNT-coated carbon cloth substrate - Rajarshi Roy; Arunava Jha; Diptonil Banerjee; Nirmalya Sankar Das; Kalyan Kumar Chattopadhyay (AIP Advances, 2013)
In this work a hybrid structure assembly of amorphous carbon nanotubes (a-CNTs) -reduced graphene oxide (RGO) has been fabricated on carbon cloth/PET substrates for enhanced edge effect assisted flexible field emission device application. The carbon nanostructures prepared by chemical processes were finally deposited one over the other by a simple electrophoretic deposition (EPD) method on carbon cloth (CC) fabric. The thin films were then characterized by X-ray diffraction (XRD), Fourier transformed infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscope (HRTEM). Field assisted electron emission measurement was performed on this hybrid structure. It was observed that the hybrid carbon nanostructure showed exceptional field emission properties with outstanding low turn-on and threshold field (Eto∼ 0.26 Vμm−1, Eth ∼ 0.55 Vμm1). These observed results are far better compared to standalone and plasma etched edge enhanced RGO systems due to the bottom layer a-CNTs bed which assisted in significant enhancement of edge effect in RGO sheets.